A Feasibility study of a cutflower growing cooperative - Aragon, Marnie; Ibarra, Celeste; Leung, Felicia; Magpili, Mylene; Picazo, Ana.; Santos, Jooz. (Diliman, Quezon City College of Engineering, 1993)
The SENTRO NG IKAUUNLAD NG KATUTUBONG AGHAM AT TEKNOLOHIYA (SIKAT), a non-government organization based in the University of the Philippines, has proposed the cutflower trade as a subject for a feasibility study. The merit of the subject as a venture project was deliberated to be worthy based on two main points. One, the presence of trade resource persons interested in the initiation of the project and to, the nature of the project being primarily a response to a need for a community based livelihood program. The prefeasibility exercise was very minimal, it being a briefing with James Esguerra, the project coordinator. It includes the outline of expectation from the study and resource persons and agencies to facilitate data gathering.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: SENTRO NG IKAUUNLAD NG KATUTUBONG AGHAM AT TEKNOLOHIYA (SIKAT); Cut flowers; Cut flowers--Marketing.; Participatory monitoring and evaluation (Project management)